2014
DOI: 10.3892/ijo.2014.2506
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 regulates TGF-α-induced epithelial-mesenchymal transition in human prostate cancer cells

Abstract: Transforming growth factor-α (TGF-α) is upregulated in advanced stages of prostate cancer and strongly correlated with metastasis. However, the effect of TGF-α on epithelial-mesenchymal transition (EMT) in prostate cancer and the underlying mechanisms remain unclear. Recently, microRNAs have emerged as new regulators of EMT. This study found that treatment of DU145 cells with TGF-α suppressed the expression of epithelial marker E-cadherin and increased the expression of mesenchymal marker Vimentin as well as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…Slug, a regulator of E-cadherin and epithelial-to-mesenchymal transition (EMT), was demonstrated to be a direct target for miR-124 in breast carcinoma cells (30). Consistent with the finding, an independent group showed that miR-124 inhibits TGF-α-induced EMT by modulating Slug in DU145 prostate carcinoma cells (31). Moreover, miR-124 was shown to negatively regulate signal transducers and activators of transcription 3 (STAT3) to reduce the tumorigenicity of colorectal and hepatocellular carcinoma cells (32, 33).…”
Section: Discussionsupporting
confidence: 75%
“…Slug, a regulator of E-cadherin and epithelial-to-mesenchymal transition (EMT), was demonstrated to be a direct target for miR-124 in breast carcinoma cells (30). Consistent with the finding, an independent group showed that miR-124 inhibits TGF-α-induced EMT by modulating Slug in DU145 prostate carcinoma cells (31). Moreover, miR-124 was shown to negatively regulate signal transducers and activators of transcription 3 (STAT3) to reduce the tumorigenicity of colorectal and hepatocellular carcinoma cells (32, 33).…”
Section: Discussionsupporting
confidence: 75%
“…Overexpression of miR-124 on the TGF-α treated PCa cells inhibited the EMT inducing effects of TGF-α and reduced cellular invasion. Further, the authors demonstrated that miR-124 directly targets Slug (Figure 1) [70]. …”
Section: Micrornas and Emt In Prostate Cancermentioning
confidence: 99%
“…Capn4 is involved in the EMT of glioma cells. miR-124 has been demonstrated to reverse the EMT (16). We investigated whether Capn4 was involved in this process.…”
Section: Mir-124 Suppresses the Migration And Invasion Of Glioma Cellmentioning
confidence: 99%